Senescence Alters PPARγ (Peroxisome Proliferator–Activated Receptor Gamma)-Dependent Fatty Acid Handling in Human Adipose Tissue Microvascular Endothelial Cells and Favors Inflammation. Issue 5 (May 2018) - Briot, Anaïs; Decaunes, Pauline; Volat, Fanny; Belles, Chloé; Coupaye, Muriel; Ledoux, Séverine; Bouloumié, Anne
Abstract : Objective—: Adipose tissue (AT) dysfunction associated with obesity or aging is a major cause for lipid redistribution and the progression of cardiometabolic disorders. Our goal is to decipher the contribution of human AT microvascular endothelial cells (ECs) in the maintenance of fatty acid (FA) fluxes and the impact of senescence on their function. Approach and Results—: We used freshly isolated primary microvascular ECs from human AT. Our data identified the endothelial FA handling machinery including FATPs (FA transport proteins) FATP1, FATP3, FATP4, and CD36 as well as FABP4 (FA binding protein 4). We showed that PPARγ (peroxisome proliferator–activated receptor gamma) regulates the expression of FATP1, CD36, and FABP4 and is a major regulator of FA uptake in human AT EC (hATEC). We provided evidence that endothelial PPARγ activity is modulated by senescence. Indeed, the positive regulation of FA transport by PPARγ agonist was abolished, whereas the emergence of an inflammatory response was favored in senescent hATEC. This was associated with the retention of nuclear FOXO1 (forkhead box protein O1), whereas nuclear PPARγ translocation was impaired. Conclusions—: These data support the notion that PPARγ is a key regulator of primary hATEC function including FA handling and inflammatory response. However, the outcome of PPARγ activation is modulated by senescence, a phenomenon that may impact the ability of hATEC to properly respond to and handle lipid fluxes. Finally, our work highlights the role of hATEC in the regulation of FA fluxes and reveals that dysfunction of these cells with accelerated aging is likely to participate to AT dysfunction and the redistribution of lipids. Abstract : Supplemental Digital Content is available in the text.